„La pena máxima” de Santiago Roncagliolo. Argentina y Perú en el Mundial de 1978 y la presentación de los cuerpos - Lucero Núñez Cueva de Andruszkiewicz, Angelina (Studia Europaea Gnesnensia, 2025)
This article delves into the depiction of the body and the process of torture in the novel “The Penalty”. By examining literary testimonies of the characters, the study explores the literary figures employed to portray various postures and silences of the body, as well as the repression perpetrated and concealed under the guise of the 1978 FIFA World Cup. Also, the author highlights the traumatic experiences of the characters, scarred by past events that remain in the collective memory.